Bakunin in the centre, Friscia on his left, Fanelli on his right. From: Movimiento Operaio. Milano (anno V) nr.3. p.464
Bakunin in the centre, Friscia on his left, Fanelli on his right. From: Movimiento Operaio. Milano (anno V) nr.3. p.464.